AKURASI METODE INSPEKSI VISUAL DENGAN ASAM ASETAT/IVA UNTUK DETEKSI DINI KANKER LEHER RAHIM - Yunita Marliana (Jurnal Kesehatan Prima, 2014)
Abstract: Cervical cancer cancers occupy third in the world after breast and lung cancer, because the symptoms did not appear at an early stage, thus referred to as the "Silent Killer". In Indonesia, cervical cancer is the most common malignancy and a leading cause of death in women in the last three decades. It is estimated that the incidence of this disease is about 100 per 100,000 population. WHO says IVA can detect pre-cancerous lesion level (high-grade lesions precanceraus) with a sensitivity of 66-96% and a specificity of 64-98%. While the positive predictive value (positive predective value) and negative predictive value (predective negative value) each between 10-20% and 92-97%. American Cancer Society (ACS) recommends screening ideally begins 3 years after the start of sexual intercourse through the vagina. Method of visual inspection with acetic acid (VIA) can be an option for people who are far from laboratory facilities and for community and town areas with inadequate access to health services, screening with cytology method would be more appropriate.